An enhanced fractal self-pumping dressing with continuous drainage for accelerated burn wound healing - Lan, Jinze; Shi, Lianxin; Xiao, Wuyi; Zhang, Xiaobin; Wang, Yuzhe; Wang, Shutao (Frontiers in Bioengineering and Biotechnology, 2023)
Massive exudates oversecreted from burn wounds always delay the healing process, accompanied by undesired adhesion, continuous inflammation, and high infection risk. Conventional dressings with limited draining ability cannot effectively remove the excessive exudates but constrain them in the wetted dressings immersing the wound bed. Herein, we fabricate an enhanced fractal self-pumping dressing by floating and accumulating hollow glass microspheres in the hydrogel precursor, that can continuously drain water at a non-declining high speed and effectively promote burn wound healing. Small hollow glass microspheres can split the fractal microchannels into smaller ones with higher fractal dimensions, resulting in higher absorption efficiency. In an in vivo burn wound model on the dorsum of murine, the enhanced fractal self-pumping dressing can significantly reduce the appearance of the wound area and alleviate tissue edema along the healing process. This study sheds light on designing high-efficiency and continuous-draining dressings for clinical applications.